APLIKASI BORDIR KOMPUTER 3 DIMENSI PADA GAUN MALAM DENGAN SUMBER IDE ILALANG - Dewi, Inas Mutiara; Yulistiana, Yulistiana (BAJU: Journal of Fashion and Textile Design Unesa, 2023)
Weeds or lying grass are often considered nuisance plants or weeds, because they easily grow anywhere on empty land. The purpose of writing this article is: (1) to describe the process of making 3-dimensional computer embroidery applications on evening dresses; (2) to describe the process of applying 3-dimensional computer embroidery applications to evening gowns; and (3) to describe the finished results of the application of 3-dimensional computer embroidery on evening gowns. Weeds can be used as a source of ideas for making a three-piece evening gown consisting of a jumpsuit, outer dress and layered skirt using fabric manipulation using a 3-dimensional computer embroidery application as a transition source for weed ideas. Computer embroidery is the newest technology today so that the process is easier and faster according to the desired design. The work engineering method starts from determining the source of ideas in the form of a moodboard, planning colors and materials, designing dresses, the process of making evening dresses, the process of making 3-dimensional computer embroidery applications starting with creating motif designs on the computer and then applying them to evening dresses. The results of changing evening gowns using fabric manipulation using 3-dimensional computer embroidery applications produce clothing that looks real, beautiful, and elegant.